An Approach to Ad-hoc Messaging Networks Using Time Shifted Propagation - Fuchß, Christoph; Stieglitz, Stefan; Hillmann, Oliver; Lattemann, Christoph (International Journal of Interactive Mobile Technologies (iJIM), 2007)
Many communication devices, like mobile phones and PDAs, are enabled for near field communication by using Bluetooth. Many approaches dealt so far with the attempt to transfer mobile ad-hoc networks (MANET) to the mechanism of the â??fixed internet